2000
DOI: 10.1016/s0014-5793(00)01165-0
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of CDSP 32, a drought‐induced thioredoxin, in the response to oxidative stress in potato plants

Abstract: In animal cells, yeast and bacteria, thioredoxins are known to participate in the response to oxidative stress. We recently identified a novel type of plant thioredoxin named CDSP 32 for chloroplastic drought-induced stress protein of 32 kDa. In the present work, we measured comparable increases in the glutathione oxidation ratio and in the level of chlorophyll thermoluminescence, a specific marker for thylakoid lipid peroxidation in Solanum tuberosum plants subjected to drought or oxidative treatments (photoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
58
0
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(65 citation statements)
references
References 34 publications
4
58
0
3
Order By: Relevance
“…CDSP32 could act more specifically during stress responses when the pool of reduced GSH decreases and/or when GSH is needed for other functions, such as the protection of carbon metabolic enzymes such as glyceraldehyde-3-phosphate dehydrogenase (40). Indeed, accumulation of CDSP32 has been shown to occur during environmental constraints, such as severe water deficit or photooxidative treatments, which result in decreases in the pool of reduced glutathione (26,27,41). Thus, the Trx could provide MSRB1 with electrons and ensure the MSRB activity level required for protection during environmental constraints (42).…”
Section: Table 2 Stoichiometry Of Msrb1 Reduction By Cdsp32mentioning
confidence: 99%
See 1 more Smart Citation
“…CDSP32 could act more specifically during stress responses when the pool of reduced GSH decreases and/or when GSH is needed for other functions, such as the protection of carbon metabolic enzymes such as glyceraldehyde-3-phosphate dehydrogenase (40). Indeed, accumulation of CDSP32 has been shown to occur during environmental constraints, such as severe water deficit or photooxidative treatments, which result in decreases in the pool of reduced glutathione (26,27,41). Thus, the Trx could provide MSRB1 with electrons and ensure the MSRB activity level required for protection during environmental constraints (42).…”
Section: Table 2 Stoichiometry Of Msrb1 Reduction By Cdsp32mentioning
confidence: 99%
“…Plants display a remarkable diversity of Trxs (1), but among the 10 plastidial Trxs assayed, only the unusual CDSP32 is able to regenerate the activity of 1-Cys MSRB1 (16). CDSP32, induced under severe abiotic stress conditions (26,27), is composed of two Trx modules, with only one potential active redox disulfide center in the C-terminal domain (26). Affinity chromatography and co-immunoprecipitation assays identified plastidial 2-Cys Prxs and 1-Cys MSRB1 as potential targets of CDSP32 (28,29).…”
mentioning
confidence: 99%
“…Genetic approaches aiming to identify functions of TRX and GRX in knockout plants have largely been limited by the absence of phenotypes of single mutants presumably due to functional redundancies among members of the multigene families of TRX and GRX (Meyer et al, 2008). In a few reports, TRXs have been shown to be involved in pathogenic responses (Rivas et al, 2004;Sweat and Wolpert, 2007;Tada et al, 2008), hypersensitiviy to oxidants (Broin et al, 2000(Broin et al, , 2002Broin and Rey, 2003), cytochrome b(6)f biosynthesis (Lennartz et al, 2001), and plasmodesmal transport in meristems (Benitez-Alfonso et al, 2009). Recently, genetic evidence has revealed functions of GRX-like proteins in flower development (Xing et al, 2005;Xing and Zachgo, 2008;Li et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…These include types f, m, x, and y (Collin et al, 2003) and additional TRXs and TRX-like proteins more recently identified, such as High Chlorophyll Fluorescence164 (Motohashi and Hisabori, 2006), Chloroplastic Drought-induced Stress Protein32 (CDSP32) (Broin et al, 2000), TRX z (Arsova et al, 2010;Chibani et al, 2010), or the family of atypical TRXs called ACHT (for Atypical Cys His-rich Trxs) (Dangoor et al, 2009). The chloroplast also contains a specific system for TRX reduction, which is dependent on ferredoxin (Fd) reduced by the photosynthetic electron transport chain and an Fd-dependent TRX reductase (FTR) (Schürmann and Buchanan, 2008).…”
Section: Introductionmentioning
confidence: 99%